Online Product Tracking and Traceability System in Manufacturer of Formula 1 Car Components EPM Technology Group - Sungur, Ersin (2012)
In today’s knowledge-intensive and collaborative manufacturing industry, an effective and efficient product tracking and traceability ability which enables companies to capture, display, and retrieval the product information is crucial. A product tracking and traceability system which provides precise manufacturing information sharing among the players in a supply chain creates a competitive advantage for companies in manufacturing industry. The main functions of an online product tracking and traceability system are monitoring the status and location of any item by means of registered identification and delivering flow of information internally and externally (to clients); generating historical data that allows traceability of information, providing information concerning manufacturing activities on a shop floor for administrative practices such as product costing, work scheduling, purchasing, etc. As an online system, it accepts input directly from the area where it is created and returns the output directly to the area where it is required. An effective online product tracking and traceability system enables companies to improve productivity and to achieve desired level of quality. This study aims to examine the opportunities associated with product tracking and traceability systems and to develop an optimal online product tracking and traceability system solution method for implementation in EPM Technology Group, Formula 1 Car Component Manufacturer Company, through combination of business, manufacturing and information system disciplines with a comprehensive literature review. Throughout this study, the benefits of an online product tracking and traceability system for a manufacturing SME will be identified, the suitable system solutions that fit to the online product tracking and traceability system definition will be evaluated and the fundamental components of an online product tracking and traceability system will be determined. In order to achieve an optimal online product tracking and traceability system solution that allows EPM Technology Group to gain accurate and rapid product identification and to improve manufacturing process monitoring capabilities on their shop floor, the administrative and manufacturing activities in EPM Technology Group will be identified and analysed. Consequently, a solution method for developing a feasible and cost-effective system to satisfy core requirements of product tracking and traceability applications, requirements of AS/9100 quality management standard and expectations of EPM Technology Group will be proposed. This study is organised mainly into two major parts. First part will cover academic and industry literature review, which provides background information relevant to the product tracking and traceability studies, and descriptions of key terms and concepts of fundamentals of product tracking and traceability systems. Besides, methodology deployed in this study will be explained in the first part. Second part will be more interested in practical work including decision-making analyses about the components of online product tracking and traceability system solution. While developing most feasible solution in line with the operational and managerial context of a specific business, structured procedures and methods will be utilised for accurate decision-making about the main components of online product tracking and traceability systems which are product identification techniques/technology, software application modules and software provider. The selection criteria will be defined for making decision about each component. Plus, a simple conceptual design solution targeting to satisfy requirements and needs of EPM Technology Group will be presented by the end of second part. Finally, recommendation for future stages of EPM’s project will be given in last chapter of this study. As outcome of this dissertation project, ideal solution alternatives and recommendations for choosing optimal product identification technology and business information system applications for product tracking and traceability practices will be provided to EPM. All of the selection criteria for making decision about the online product tracking and traceability system components and selection procedure for choosing system software provider (vendor) can be used as a guideline for similar software and system sourcing practices in EPM Technology Group. Although the main topic of this study is concentrated on manufacturing processes, the managerial content of this study which examines various administrative practices will provide a gateway to EPM Technology Group to manage their future operations more effective and more efficient. More specifically, the EPM Technology Group management can use this study as a reference while establishing online product tracking and traceability system and co-operating with software providers.